PELATIHAN PRODUKSI BIOLISTRIK DARI LIMBAH TAHU PADA KARANG TARUNA DESA KARANGSOKA - Indah Sulistiyawati; Andika Ristiono (LP2M Universitas Hasanuddin, 2022)
Karangsoka Village is a densely populated area with most of the people belonging to the lower middle-class economy and diverse livelihoods. Based on the measurement data of the Building Village Index (IDM) with the Standard Operating Procedure (SOP) updating the status of the IDM village development in 2019, Karangsoka Village is included in the status of a developing village. The problem that has occurred is that environmental pollution in the past year has been found in water and air from the production process of the Small and Medium Industry (IKM) tofu, resulting in mild health problems, and the pollution occurs in river bodies. The above problems can be overcome by the Stimulus Community Partnership Program (PKMS) activity, namely training to improve the skills of tofu waste management skills given to youth groups. to be directly involved in the prevention of environmental pollution. PKMS activities consist of: (1) coordination, (2) program socialization, (3) counseling, (4) training, (5) piloting, and (6) monitoring and evaluation. Training activities for tofu liquid waste treatment using appropriate technology, namely microbial fuel cell (MFC). The results of PKMS activities produce non-physical and physical outcomes. The non-physical result is an increase in the knowledge and skills of youth groups by 36% in managing tofu liquid waste to produce bio-electricity. The physical results are the demonstration of the use of lighting from the bio-electricity of tofu liquid waste at the community business center and the surrounding environment. — Desa Karangsoka merupakan daerah padat penduduk dengan sebagain besar masyarakatnya tergolong ekonomi menengah ke bawah dan mata pencaharian yan beragam. Berdasarkan data pengukuran Indeks Desa Membangun (IDM) dengan Standar Operasional Prosedur (SOP) pemutakhiran status perkembangan desa IDM tahun 2019, Desa Karangsoka masuk dalam status desa berkembang. Permasalahan yang telah terjadi yaitu pencemaran ligkungan dalam setahun terakhir terdapat pada perairan dan udara dari proses produksi Industri Kecil Menengah (IKM) tahu, sehingga berakibat menyebabkan gangguan kesehatan ringan, dan pencemaran tersebut timbul pada badan sungai. Permasalahan diatas dapat diatasi dengan kegiatan Program Kemitraan Masyarakat Stimulus (PKMS) yaitu pelatihan peningkatan skill ketrampilan pengelolaan limbah tahu yang diberikan kepada kelompok pemuda karang taruna.Tujuan dari kegiatan PKMS ini adalah mengelola limbah cair tahu dengan memanfaatkan sebagai bahan biolistrik dan memberdayakan kelompok pemuda karang taruna untuk terlibat langsung dalam penaggulangan pencemaran lingkungan. Kegiatan PKMS terdiri dari: (1) koordinasi, (2) sosialiasi program, (3) penyuluhan, (4) pelatihan, (5) percontohan, dan (6) monitoring dan evaluasi. Kegiatan pelatihan pengolahan limbah cair tahu dengan menggunakan teknologi tepat guna yaitu microbial fuel cell (MFC). Hasil kegiatan PKMS menghasilkan luaran non fisik dan fisik. Hasil non fisik yaitu adanya peningkatan pengetahuan dan skill ketrampilan pemuda karang taruna sebesar 36% dalam mengeloa limbah cair tahu untuk memproduksi biolistrik. Adapun hasil fisik yaitu adanya percontohan penggunaan pene-rangan dari biolistrik limbah cair tahu pada sentra usaha masyarakat dan lingkungan sekitar.